2011
DOI: 10.1007/s10880-011-9272-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Illness Perceptions as Related to Mammography Uptake in Randomly Selected Women in Greece

Abstract: Previous research has shown that, although routine mammography screening can reduce mortality from breast cancer, the use of annual mammography screening remains well under 65%. In an effort to determine the factors that are associated with women's mammography behaviors, this study used the health belief model and the common-sense model of self-regulation as the theoretical frameworks to explore health beliefs, illness representations, and women's mammography practice. Data were obtained from a nationally repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…[18] A study conducted in Greece suggested that women who perceived fewer benefits and more barriers to mammography screening, and who have more negative emotional representations of breast cancer or no private health insurance coverage were more likely to have no screening mammography. [19] Based on these above studies, behavioral interventions, theory-based education, and interventions targeted at physicians or providers were effective to promote screening.…”
Section: Introductionmentioning
confidence: 99%
“…[18] A study conducted in Greece suggested that women who perceived fewer benefits and more barriers to mammography screening, and who have more negative emotional representations of breast cancer or no private health insurance coverage were more likely to have no screening mammography. [19] Based on these above studies, behavioral interventions, theory-based education, and interventions targeted at physicians or providers were effective to promote screening.…”
Section: Introductionmentioning
confidence: 99%
“…The extant literature suggests that a number of factors influence BS uptake, namely: (1) health beliefs [1719], (2) illness representations [17, 20, 21], (3) knowledge of BC signs and symptoms, its causes and consequences, and recommended BS practices [22, 23], (4) socio-demographic factors [22, 24, 25], and (5) health status (medical factors) [17, 2527]. …”
Section: Introductionmentioning
confidence: 99%
“…The Health Belief Model (HBM) was selected as one of the theoretical models for the current study, as it is widely used to identify associated variables with mammography and guides the prediction of screening behaviours [17, 18]. The HBM consists of six constructs: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy [28, 29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on illness perceptions in patients with breast cancer illustrates the clinical and scientific value of self-regulation model, as can be seen in Table 1 in which a substantial number of empirical studies available on this topic is summarized (Anagnostopoulos et al, 2012;Anagnostopoulos & Spanea, 2005;Beadle et al, 2004;Duric et al, 2007;Frith & Harcourt, 2007;Hunter, Grunfeld, & Ramirez, 2003;Kucukkaya, 2010;Kwate, Thompson, Valdimarsdottir, & Bovjberg, 2005;Lavery, & Clarke, 1996;McCorry et al, in press;Millar, Purushotham, McLatchie, George, & Murray, 2005;Mulders, Vingerhoets, & Breed, 2008;Rozema, Völlink, & Lechner, 2009;Silva, Moreira, & Canavarro, 2012;Thuné-Boyle, Myers, & Newman, 2006).The results of the studies show how various dimensions of illness perceptions are associated with different aspects of (medical or behavioral) outcome.…”
Section: Introductionmentioning
confidence: 99%